1985
DOI: 10.1080/00268978500100311
|View full text |Cite
|
Sign up to set email alerts
|

Test of a simple analytic model for fluids of hard linear molecules

Abstract: Pynn has proposed (1974, J. chem. Phys., 60, 4579) a simple, empirical generalization for fluids of hard linear molecules of the Percus-Yevick direct correlation function for hard spheres. We make a detailed numerical study of this analytic model for hard dumbells, including comparisons with the true Pereus-Yevick results, and find that it is surprisingly effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
2
3
1
Order By: Relevance
“…The angular dependence thus introduced possesses plausible characteristics just because of this coupling to a, on the other hand Lado (1985) showed that it has the deficiency of giving an isotropic value for c< 2 )(r -» 0), which is contrary to reality. Lado also tested the decoupling approximation by comparing it with the integral equation approach for hard dumbbells and found excellent agreement for the case of a separation of 0.4 times the diameter of the composing spheres.…”
Section: Integral Equation Approachcontrasting
confidence: 41%
See 1 more Smart Citation
“…The angular dependence thus introduced possesses plausible characteristics just because of this coupling to a, on the other hand Lado (1985) showed that it has the deficiency of giving an isotropic value for c< 2 )(r -» 0), which is contrary to reality. Lado also tested the decoupling approximation by comparing it with the integral equation approach for hard dumbbells and found excellent agreement for the case of a separation of 0.4 times the diameter of the composing spheres.…”
Section: Integral Equation Approachcontrasting
confidence: 41%
“…behaviour at higher densities, with attractive interactions and for bidisperse systems), they do not lead to the exact result of Onsager for infinitely thin hard rods. There are also some other models based on the wormlike chain which we can only mention here: an extension of the Flory theory to wormlike chains (Ronca and Yoon 1982, 1985 and theories using a Maier-Saupe potential (Ten Bosch et al 1983, \torner et al 1985. As a last point we want to draw attention to some monographs and review papers on liquid crystals (De Gennes 1974, Stephen and Straley 1974, Chandrasekhar 1977, Luckhurst and Gray 1979, Vertogen and De Jeu 1988, Frenkel 1991 and liquid crystalline polymers (Straley 1973a, Blumstein 1978, Grosberg and Khokhlov 1981, Ciferri et al 1982, Miller 1982, Samulski and DuPré 1983, Gordon and Plate 1984, Khokhlov and Semenov 1985, Ciferri and Marsano 1987, Semenov and Khokhlov 1988, DuPré and Yang 1991, which might be helpful for the reader.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown moreover that for hard dumbbells [7] the ansatz provided by (4) agrees surprisingly well with the numerical solutions of the PY equation. The approximation underlying (4) is most clearly exhibited by observing [8] that when (4) is used in (2) for a nematic phase it automatically leads to a decoupling of the angular and radial variables.…”
supporting
confidence: 63%
“…Since in this approach the influence of relative orientation is decoupled from the influence of interparticle distance, the name decoupling approximation is appropriate. It has the defect, first noticed by Lado, [165] that for r + 0 the direct correlation function is predicted to be isotropic, contrary to reality.…”
Section: (426)mentioning
confidence: 89%